(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Contact lens wearing is connected with microtraumatism of the corneal epithelium and the presence of hypoxia in anterior eye tissues. Purpose. To study values of the oxidation-reduction potential and markers of lipid peroxidation in the tear of extended wear soft contact lens wearers. Material and Methods. Patients were divided into two groups: Study Group, 20 patients (40 eyes) with mild/moderate myopia with extended soft contact lens wear; Control Group, 13 patients (24 eyes) with mild/moderate myopia, spectacles wearers. Results. A level of reduced glutathione in Study Group was by 18.3% lower than that in Control Group (p <0.05). A level of oxidized glutathione in Study Group was increased by 21%compared to Control Group (p <0.05). A level of malondialdehyde in Study Group was increased by 27.1 % compared to Control Group (p <0.05). A level of diene conjugates was icreased in Study Group, comprising 118% compared to controls (p> 0.05). Conclusions. Extended soft contact lens wear disrupts the prooxidant-antioxidant balance in the anterior eye tissues, particularly in the cornea. There is activation of free radical processes and reduction of antioxidant reserves, which is expressed in the increase of normal content of lipid peroxidation products in the tear and violation of glutathione balance. Such metabolic changes in the eye require an antioxidant therapy.